Flutter Framework Mobile Application Development of Gamified Automotive Reseller Team Management - Edmund Johnson; Gunawan Wang (Jurnal Info Sains : Informatika dan Sains, 2023)
Expanding company digitalization procedure can be considered a task any company should take into consideration. This also applies to sales and marketing division in a company. Gamification is considered one of various ways to apply digitalization, mainly in sales teams. A gamified model of automotive reseller team management was developed as a solution in order to answer the issue stated above. To aid in applying gamification mechanics into application development, System Development Life Cycle (SDLC) waterfall method was used in this research. In making the gamified system into reality in the form of mobile application, Flutter development was used, considering its versatile cross-platform mobile application environment and ease of development.